Biphasic Alterations in Expression and Subcellular Localization of MUC1 in Pancreatic Ductal Carcinogenesis in Syrian Hamsters. Issue 1 (January 2015) - Kitahashi, Tsukasa; Takahashi, Mami; Imai, Toshio
<x xml:space="preserve">Abstract</x> Objectives The aim of the present study was to characterize molecular targets for the prevention/diagnosis of pancreatic cancer using a chemically induced hamster pancreatic carcinogenesis model, in which background injuries to the parenchyma, for example, chronic pancreatitis or acinar atrophy, are limited. Methods Gene expression profiles in atypical hyperplasias were first investigated using a microarray technique. Immunohistochemical analyses of early lesions and invasive ductal carcinoma (IDC) were then conducted for MUC1, of which mRNA levels were prominent among the up-regulated genes, in contrast with the coexpression of epithelial-mesenchymal transition (EMT)-related proteins. Results Immunohistochemistry for MUC1 cytoplasmic domain (MUC1-CD), which was not detected in normal-like pancreatic ducts, was positive in the apical surfaces of the epithelia of hyperplasias with and without atypia and IDC areas with distinct tubular patterns. In contrast, cytoplasmic/nuclear positivity for MUC1-CD was observed in the invasive front of IDCs. The coexpression of EMT-related proteins, such as slug and vimentin, with cytoplasmic/nuclear MUC1-CD was also detected. Conclusions Alterations in the expression and subcellular localization of MUC1 represent a biphasic phenomenon, and the latter may be associated with EMT in pancreatic carcinogenesis in hamsters, which indicates that changes in MUC1 are important targets for pancreatic cancer prevention and chemotherapy.